1997
DOI: 10.1021/jm970177c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tubulin Polymerization by 5,6-Dihydroindolo[2,1-a]isoquinoline Derivatives

Abstract: 6-Alkyl-12-formyl-5,6-dihydroindolo[2,1-alpha]isoquinolines have been shown to inhibit the growth of human mammary carcinoma cells by an unknown mode of action. One of the possible molecular targets is the tubulin system which is involved in cell division. A number of 5,6-dihydroindolo[2,1-alpha]isoquinolines with methoxy or hydroxy groups in positions 3, 9, and/or 10 and various functional groups such as formyl, acetyl, cyano, alkylimino, and alkylamino in position 12 were synthesized and evaluated for both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 28 publications
4
59
0
Order By: Relevance
“…This series of compounds showed a cytostatic effect related to their tubulin polymerization inhibition (Table II). 34 The 2-phenylindoles were obtained by reacting ring-substituted anilines with bromoacetophenones in N,N-dimethylaniline (DMA) at 170 C following the Bischler method. Formylation at position 3 of indole was achieved by the Vilsmeier reaction by reacting 2-phenylindoles with DMF and POCl 3 .…”
Section: A 3-formyl-2-phenylindolesmentioning
confidence: 99%
“…This series of compounds showed a cytostatic effect related to their tubulin polymerization inhibition (Table II). 34 The 2-phenylindoles were obtained by reacting ring-substituted anilines with bromoacetophenones in N,N-dimethylaniline (DMA) at 170 C following the Bischler method. Formylation at position 3 of indole was achieved by the Vilsmeier reaction by reacting 2-phenylindoles with DMF and POCl 3 .…”
Section: A 3-formyl-2-phenylindolesmentioning
confidence: 99%
“…1 A series of indolo[2,1- a ]isoquinoline compounds have been shown to possess a wide range of biological activities, including cytostatic, 2,3 antiviral, 4 immunosuppressive 5 and tubulin polymerization inhibiting activities. 6 Another series of compounds known as metosenes have shown significant antitumor activity. 7 However, the fully aromatic pyridoindole core has been mentioned in the literature only briefly, mainly due to the challenges in the preparation of this system.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, studies on the biological activity of 5,6‐dihydroindolo[2,1‐ a ]isoquinolines have revealed promising results to advance in the treatment of manifold diseases. For instance, compounds 1 a and 1 b strongly inhibit tubulin polymerization and the growth of human breast cancer cells in vitro,, whereas compound 1 c is a melatonin agonist (Figure ) . Modern synthetic methods towards the 5,6‐dihydroindolo[2,1‐ a ]isoquinoline skeleton rely on the intramolecular cyclization of N ‐aryl‐1,2,3,4‐tetrahydroisoquinolines .…”
Section: Figurementioning
confidence: 99%